Measurement of viscoelasticity of UV photoresist used for nanoimprint lithography under confinement in nanometer-sized gaps. (11th May 2017) - Itoh, Shintaro; Takahashi, Kazuhiro; Fukuzawa, Kenji; Zhang, Hedong
Abstract: In UV nanoimprint lithography, the viscoelasticity of a photoresist is a dominant factor that affects defect control, throughput, and alignment accuracy, all of which are important for high-volume manufacturing. During the nanoimprint process, the photoresist is confined in nanogaps and nanocavities, between the mold and the substrate. In this study, we measure the viscoelasticity of a UV photoresist, PAK-01, confined in nanometer-sized gap widths by the sensitive shear force measurement method developed in our previous study. Experimental results show that PAK-01, a viscous liquid in the bulk state, turns into a viscoelastic liquid in the nanogaps. Qualitatively, a similar transition is observed with the typical acrylate monomer, isobornyl acrylate. These findings are significant factors that should be considered in the improvement of the accuracy and efficiency of nanoimprint lithography.